SEMANGAT DAN KOMITMEN BERWIRAUSAHA UNTUK MENINGKATKAN PEREKONOMIAN PELAKU UMKM P4MAD MELALUI KUNJUNGAN WISATAWAN - Unun Rahmasari; Sutrisno; Fadjar Darmaputra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to analyze, whether having a HR strategy with high entrepreneurial enthusiasm and commitment can increase economic figures through tourist visits by Micro, Small and Medium Enterprises (MSMEs) at the Association of Traders Pujasera Tourism of the Great Mosque of Demak (P4MAD). The data collection for this study was by distributing questionnaires which would be processed using the Quantitative research method using the SmartPLS 3 application. The results of the data that have been processed, Morale has a positive effect on increasing Tourist Visits with a P-Value of (0.000). Work Commitment has less effect on increasing Tourist Visits with a P-value of (0.75). Tourist visits have a positive effect on increasing the economy with a P-Value of (0.000). Work enthusiasm is less influential in improving the economy with a P-Value having a value of (0.239). work commitment is less influential in improving the economy with a P-Value that has a value of (0.754). Morale has a positive effect on increasing the economy through tourist visits with a P-Value of (0.000). And Work Commitment is less influential in improving the economy through tourist visits with a P-Value of (0.754). Future initiatives after this research, MSME actors in P4MAD can improve strategies, to be more innovative, and can use E-HRM, which is a method used for managing HR (Human Resources) aimed at attracting tourist visits and increasing economic numbers